(untitled) (Journal of the College of Basic Education, 2022)
In this research، The structural properties of( MgO1-xCdSx ) thin films deposited by spray pyrolysis technique on glass substrates at (400°C) with different CdS doping ratio% (0,2,4,6,8) .The results of (XRD) show that all film Polycrystalline with preferred orientation along(200) and (MgO) thin film has acubic crystalline structure . With CdS doping shows hexagonal structure increase clarity with increase doping ratio . The topography of the surface ، which was carried out using Field Emission Scanning Electron Microscopy (FE-SEM) showed that the surface of the films consist of the nanoparticles with cauliflower like structures and the grain size decreasing with increase CdS concentrations